Akulturasi Budaya Indonesia dalam Implementasi Hukum Keluarga Islam - Mohamad Badrun Zaman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The formation of Islamic family law certainly cannot be separated from the various cultures that exist in Indonesia. For this reason, this study aims to find out how the acculturation of Indonesian culture in the application of Islamic family law in Indonesia. The method used is a qualitative descriptive approach with data analysis in the form of literature reviews from primary data and secondary data obtained from various literature studies. The results of the study show that culture in Indonesia is always undergoing evolution where this can create cultural acculturation with high enthusiasm which in the end creates the Arabization of Islam. This cultural acculturation process has indeed created various reforms in the legal system in Indonesia, including regarding Islamic religious culture which has begun to mushroom in the community, especially due to the domination of Muslims in Indonesia. Thus, Islamic family law is also guided by the phase of cultural acculturation which is considered the most appropriate to the conditions of Indonesian society.